Gastrointestinal parasitic infection in the hazel grouse Tetrastes bonasia in France. Issue 2 (1st April 2021) - Fanelli, Angela; Tizzani, Paolo; Belleau, Eric
Abstract : The hazel grouse Tetrastes bonasia is a Galliformes species of major conservation interest and threatened throughout Europe. However, little information is currently available on its sanitary status both in the Alps and worldwide. Considering that gastrointestinal parasites are one of the factors negatively impacting on Galliformes population dynamics, the objective of this study is to fill the gaps of knowledge on the parasite‐fauna of the Alpine hazel grouse. Twenty‐nine hazel grouse were collected in the French Alps during the period 1987–2019 (no samples collected during 1997–1999). All birds were searched for gastrointestinal parasites utilizing conventional parasitological techniques. Prevalence, intensity of infection and abundance (mean number of parasites) were calculated for each parasite species. In addition, parasite richness was evaluated. Forty‐one percent (CI95% : 23.4–59.3) of birds harboured parasites, belonging to seven parasite species. Capillaria caudinflata was the most common with a prevalence of 27.6% (CI95% : 11.3–43.8), whereas Eimeria spp. was found with a prevalence of 10.3% (CI95% : 0–21.4). For both parasites, the majority of the infected animals show low parasite load. A low prevalence (3.4% – CI95% : 0–10.1) was detected for Capillaria anatis, Heterakis gallinarum, Raillietina sp., Dispharynx nasuta and Trematodes. To our knowledge, this is the first report of C. anatis and D. nasuta in the hazel grouse, and in general one of the few article providing information on hazel grouse parasite community. Overall, the parasite richness was very low, with 75% of the infected birds carrying one parasite species, 17% two species and only one bird (8%) with three species. This study increases the scarce literature available on the hazel grouse parasites. The epidemiological descriptors reported are particularly useful to compare the parasite‐fauna of the hazel grouse across locations and time periods.